MULTIPARTITE RAMSEY NUMBERS FOR PATHS - SY (NIM: 30104003), SYAFRIZAL
Ramsey (1930) introduced a theory concerning the finding of a procedure to determine the consistency of given logical formulas. The theory is known as Ramsey theory. ErdAos and Szekeres (1935), then, applied this theory into graphs. Ramsey theory has some applications in mathematics, information theory, computation, and economics (Espino, 2004). In mathematics, besides graph theory, Ramsey theory also has grown and expanded in number theory, algebra, geometry, topology, harmonic analysis, metric space, and ergodic theory (Rosta, 2004).